2011
DOI: 10.4162/nrp.2011.5.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dietary quality of adolescents using Healthy Eating Index

Abstract: The aim of this study was to use the Healthy Eating Index-2005 (HEI-2005) to assess diet quality and determine the relationship between the HEI-2005 and the energy and nutrient intakes of adolescents. A cross-sectional study was conducted on 1,104 healthy adolescents, mean age of 15.8 ± 1.24 years. Dietary intake was measured with the 24-hour dietary recall method, and dietary quality was assessed by means of the HEI-2005. Diet quality scores ranged from 23.7 to 77.5. The mean score was found to be 51.5 ± 9.07… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 34 publications
(61 reference statements)
3
24
0
1
Order By: Relevance
“…Although an increasing number of studies have employed diet indices to describe diet quality in children and adolescents [12-14,16-20,22-24,28,51,54-56], none have been conducted in NZ. Six studies have reported the validity of a diet index against an independent reference method among populations which included adolescents aged 13 years and above [17,20,23,28,51,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an increasing number of studies have employed diet indices to describe diet quality in children and adolescents [12-14,16-20,22-24,28,51,54-56], none have been conducted in NZ. Six studies have reported the validity of a diet index against an independent reference method among populations which included adolescents aged 13 years and above [17,20,23,28,51,54].…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of diet quality among adolescents has tended to use both food and nutrient-based diet indices such as the Healthy Eating Index [11-13] and its derivatives [14,15]. These diet indices were adapted from those originally developed for adults based on the United States Dietary Guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the HEI-2005 comprises 12 components, which are scored on a scale from 0 to maximum ( M ), where M is 5, 10, or 20 according to the component. Thus, the composite HEI score can potentially range from a minimum of zero to a maximum score of 100, with 100 points referring to perfect diet quality and lower results indicating larger deviations from the recommended intakes [ 7 ]. For each individual and each component, the ratio of the reported intake of food group (relevant to the HEI component considered) to the reported energy intake was also calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in high income countries attribute disparities in obesity and health in part to differences in diet quality [68]. For most high income countries in general, energy-dense foods cost less, whereas healthier foods tend to cost more [7, 9, 10]; thus, diet quality may differ by socioeconomic status (SES) [9, 11].…”
Section: Introductionmentioning
confidence: 99%